European Journal of Clinical Pharmacology - Dahlqvist, Rune.; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
The European Journal of Clinical Pharmacology publishes original papers on all aspects of clinical pharmacology and drug therapy in humans. Manuscripts are welcomed on the following topics: therapeutic trials, pharmacokinetics/pharmacodynamics, pharmacogenetics, drug metabolism, adverse drug reactions, drug interactions, all aspects of drug development, development relating to teaching in clinical pharmacology, pharmacoepidemiology, and matters relating to the rational prescribing and safe use of drugs. Methodological contributions relevant to these topics are also welcomed. Data from animal experiments are accepted only in the context of original data in man reported in the same paper. EJCP will only consider manuscripts describing the frequency of allelic variants in different populations if this information is linked to functional data or new interesting variants. Highly relevant differences in frequency with a major impact in drug therapy for the respective population may be submitted as a letter to the editor. Straightforward phase I pharmacokinetic or pharmacodynamic studies as parts of new drug development will only be considered for publication if the paper involves a compound that is interesting and new in some basic or fundamental way, or methods that are original in some basic sense, or a highly unexpected outcome, or conclusions that are scientifically novel in some basic or fundamental sense. Straightforward descriptive data in drug utilization will only be considered if more than one geographical area is studied and if a scientific hypothesis is tested or an intervention carried out. Descriptive data in drug utilization can however be quite useful in a more local setting. Again, if conceptually new methods, analysis, or ways of reasoning are involved, this would elicit greater interest from the international scientific community. In such a case, we would welcome submission to the EJCP and evaluate the paper according to standard procedures. The Journal also accepts review articles on various topics related to drug action in man. Debate on controversial issues is also encouraged, usually in the form of a letter to the editor that comments on a paper published in the Journal. Case reports on new findings or a new understanding of a mechanism of action should usually also be submitted in the form of a letter to the editor.
Keywords: Pharmacology; Pharmacology/Toxicology.